Deviatoric Stress Evolution Laws and Control in Surrounding Rock of Soft Coal and Soft Roof Roadway under Intense Mining Conditions. (22nd June 2020) - Chen, Dongdong; Ji, Chunwei; Xie, Shengrong; Wang, En; He, Fulian; Cheng, Qiong; Zhang, Qing
Abstract : Aiming at the problem of large deformation and instability failure and its control of soft coal and soft roof roadway under intense mining, laboratory experiments, theoretical calculations, Flac 3D numerical simulation, borehole peeping, and pressure observation were used to study the deflection characteristics of the deviatoric stress of the gas tailgate and the distribution and failure characteristics of the plastic zone in the mining face considering the strain softening characteristics of the roof and coal of roadway, and then the truss anchor cable-control technology is proposed. The results show the following: (1) The intense mining influence on the working face will deflect the peak deviatoric stress zone (PDSZ) of the surrounding rock of the gas tailgate. The influence distance of PDSZ is about 20 m in advance and 60 m in lag; the PDSZ at the gob side of the roadway is located in the range of 3–5.5 m from the surface of the coal pillar, while the coal wall side is mainly located in the range of 3–4.5 m at the shoulder corner and bottom corner of the solid coal. (2) The intense mining in the working face caused the nonuniform expansion of the surrounding rock plastic area of the gas tailgate. The two shoulder angles of the roadway and the bottom of the coal pillar have the largest damage range, and the maximum damage location is the side angle of the coal pillar (5 m). Angle and bottom angle of coal pillar are the key points of support control. (3) The plastic failure line of the surrounding rock of the gas tailgate is always between the inner and outer contours of the PDSZ, and the rock mass in the PDSZ is in a stable and unstable transition state, so the range of anchor cable support should be cross plastic failure line. (4) The theoretical calculations and numerical simulation results agree well with the drilling peep results. Based on the deflection law of the PDSZ and the expansion characteristics of the plastic zone, a truss anchor cable supporting system with integrated locking and large-scale support function is proposed to jointly control the roof and the two sides, which effectively solves the problem of weak surrounding rock roadway under severe mining deformation control problems realizing safety and efficient production in coal mines under intense mining.